Impact of air pollution on the concentration of nitric oxide in the exhaled air (FeNO) in children - a review of the literature on the subject - Czubaj-Kowal, Marta; Kurzawa, Ryszard; Nowicki, Grzegorz (Journal of Education, Health and Sport, 2022)
The health burden related air pollution has serious implications for human health around the world. Air pollution affecting the human body includes a broad scope of health signs, starting from the mildest symptoms and ending up with death. Children, especially the youngest, due to their developmental period and associated immaturity of their systems, are more vulnerable to the penetration and concentration of air pollutants in the respiratory tract, as well as to their toxic effects. The measurement of concentration of nitric oxide in the exhaled air (FeNO) is a valuable and quite simple diagnostic method providing significant information on pathological processes in the respiratory system. This is a valuable biomarker and determinant in detecting and monitoring the upper and lower respiratory tract inflammation, especially eosinophilic inflammation, asthma and allergic rhinitis. The aim of this work is to present the measurement of the concentration of nitric oxide in the exhaled air (FeNO) as a simple method useful in the health assessment of a paediatric patient, as well as to indicate how air pollutants affect the FeNO concentration levels based on the available professional literature. Numerous research papers have revealed a correlation between the FeNO concentration levels and air pollution. It is of key importance to carry out further studies in order to assess the impact of gaseous and particulate air pollutants on the FeNO concentration levels.